Analysis of a synthetic jet-based electronic cooling module - Jagannatha, Deepak; Narayanaswamy, Ramesh; Chandratilleke, Tilak (Taylor and Francis, 2009)
This article presents a numerical study of an electronic cooling module using a periodic jet flow at an orifice with net zero mass flux, known as a synthetic jet. The two-dimensional time-dependant numerical simulation models the unsteady synthetic jet behavior, the flow within the cavity and the diaphragm movement while accounting for fluid turbulence using the shear-stress-transport (SST) k-ω turbulence model. Computations are performed for a selected range of parameters and the boundary conditions to obtain the heat and fluid flow characteristics of the entire synthetic jet module. The numerical simulation aptly predicts the sequential formation of the synthetic jet and its intrinsic vortex shedding process while accurately illustrating the flow within the cavity. It is indicated that the thermal performance of the synthetic jet is highly dependant on the oscillating diaphragm amplitude and frequency. At the heated surface, this jet impingement mechanism produces a very intense localized periodic cooling effect that reaches a peak with a time lag relative to the top displacement position of the diaphragm. The overall heat transfer rate of the synthetic jet module is about 30% better than an equivalent continuous jet. When compared to pure natural convection the enhancement varies from 20 to 120 times in the range of parameters studied.The study clearly identifies the outstanding thermal potential of the synthetic jet module for intense electronic cooling applications and its ability to operate without additional fluid circuits.